Espaços não formais na prática pedagógica de professores de Ciências nos municípios de Primavera e Quatipuru - Nordeste Paraense - OLIVEIRA, Hugo Edilberto Ramos de (2024)
The use of informal spaces has been used by elementary school teachers because these environments allow students to learn in a practical and experimental way, develop social skills, and encourage creativity and innovation. This research analyzes the use of informal spaces based on the conceptions and experiences of teachers from the state of Pará, Brazil. The investigation was developed through the application of a questionnaire to six science teachers working in the municipalities of Primavera and Quatipuru, located in the northeast of the state of Pará. As a result, we found that despite the recognition that the use of informal spaces contributes to the strengthening of teaching and student learning, this teaching practice is still a challenge for teachers working in these municipalities due to some difficulties faced, such as: releasing students to take classes in informal spaces, the incentive to carry out this teaching practice, gaps in initial and continuing education; and also difficulties with transportation. Although this teaching method presents some obstacles, teachers consider the use of non-formal spaces to be essential to contribute to the teaching and learning of students and also consider that they provide aspects that facilitate contextualized pedagogical practices in the Science discipline.